Pengaruh Model Pembelajaran Problem Based Learning Berbasis Media Visual Terhadap Kemampuan Menulis Teks Puisi Siswa Kelas X SMA Islam Az-Zahrah Palembang - Layal, Nurul; Effendi, Darwin; Puspita, Yenny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This research was conducted to determine the poetry learning outcomes of students of class XIslamic Senior High School Az-Zahrah Palembang using visual media with a problem based learning model. The research method used is an experimental type of post-test control design. Inthis study using a test technique. The final result of the evaluation of student learning data uses thet-test of the SPSS version 22 program. That is, if the required sig value is > 0.05, the data will behomogeneously distributed. If the value of sig < 0.05 then the data distribution is not homogeneous. The significant value obtained from the calculation results is the sig value of 0.88which means > 0.05. Therefore, the researcher concludes that the problem-based learning modelbased on visual media has an effect on the ability to write poetry texts for the tenth grade studentsof Islamic Senior High School Az-Zahrah Palembang.